Genome Size in Diploids, Allopolyploids, and Autopolyploids of Mediterranean Triticeae. (30th May 2010) - Eilam, T.; Anikster, Y.; Millet, E.; Manisterski, J.; Feldman, M.
Abstract : Nuclear DNA amount, determined by the flow cytometry method, in diploids, natural and synthetic allopolyploids, and natural and synthetic autopolyploids of the tribe Triticeae (Poaceae) is reviewed here and discussed. In contrast to the very small and nonsignificant variation in nuclear DNA amount that was found at the intraspecific level, the variation at the interspecific level is very large. Evidently changes in genome size are either the cause or the result of speciation. Typical autopolyploids had the expected additive DNA amount of their diploid parents, whereas natural and synthetic cytologically diploidized autopolyploids and natural and synthetic allopolyploids had significantly less DNA than the sum of their parents. Thus, genome downsizing, occurring during or immediately after the formation of these polyploids, provides the physical basis for their cytological diploidization, that is, diploid-like meiotic behavior. Possible mechanisms that are involved in genome downsizing and the biological significance of this phenomenon are discussed.